Proliferating cell nuclear antigen in gonad and associated storage tissue of the Pacific oyster Crassostrea gigas: seasonal immunodetection and expression in laser microdissected tissues - Franco, Alban; Jouaux, Aude; Mathieu, Michel; Sourdaine, Pascal; Lelong, Christophe; Kellner, Kristell; Heude Berthelin, Clothilde (Cell and Tissue Research, 2010)
International audience To understand the processes involved in tissue remodeling associated with the seasonal reproductive cycle of the oyster Crassostrea gigas, we used immunodetection and expression measurements of proliferating cell nuclear antigen (PCNA). The expression of the PCNA gene was measured by real-time polymerase chain reaction in the whole gonadal area compared with laser microdissected gonad and storage tissue. Results underlined the advantage of the laser microdissection approach to detect expression, mainly for early stages of spermatogenesis. In the storage tissue, PCNA expression was reduced in the gonadal tubules, but immunolabeled hemocytes and vesicular cells were detected when the storage tissue was being restored. In the gonadal tubules, the PCNA gene was more highly expressed in males than in females. As soon as spermatogenesis was initiated, PCNA expression showed a high and constant level. In females, the expression level increased gradually until the ripe stage. The immunological approach established the involvement of peritubular cells in gonadal tubule expansion during early gametogenesis. In both sexes, gonial mitosis was immunodetected throughout the reproductive cycle. In males, the occurrence of two types of spermatogonia was ascertained by differential immunolabeling, and intragonadal somatic cell proliferation was noted. As expected, immunolabeling was never observed from stage II spermatocytes to spermatozoa. In females, positively stained cells were detected from oogonia to growing oocytes with various labeled intracellular locations.